2014
DOI: 10.1186/1471-2369-15-23
|View full text |Cite
|
Sign up to set email alerts
|

Inter-study reproducibility of arterial spin labelling magnetic resonance imaging for measurement of renal perfusion in healthy volunteers at 3 Tesla

Abstract: BackgroundMeasurement of renal perfusion is a crucial part of measuring kidney function. Arterial spin labelling magnetic resonance imaging (ASL MRI) is a non-invasive method of measuring renal perfusion using magnetised blood as endogenous contrast. We studied the reproducibility of ASL MRI in normal volunteers.MethodsASL MRI was performed in healthy volunteers on 2 occasions using a 3.0 Tesla MRI scanner with flow-sensitive alternating inversion recovery (FAIR) perfusion preparation with a steady state free … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
48
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 29 publications
10
48
1
Order By: Relevance
“…This impression is confirmed by the numerical results in Table 3 for brain (frontal and parietal white and gray matter), liver, and kidney (cortex and medulla). Because a comprehensive determination of in vivo data for various tissues is outside the scope of this work, the present results are only compared to some most recent literature findings [16][17][18]. As it turns out all T1 values are close to published data.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…This impression is confirmed by the numerical results in Table 3 for brain (frontal and parietal white and gray matter), liver, and kidney (cortex and medulla). Because a comprehensive determination of in vivo data for various tissues is outside the scope of this work, the present results are only compared to some most recent literature findings [16][17][18]. As it turns out all T1 values are close to published data.…”
Section: Resultsmentioning
confidence: 79%
“…For experimental details see Table 1, numerical results are given in Table 3. Kidney medulla 1.75 ± 0.09 1.75 ± 0.08 1.77 ± 0.05 1.65 ± 0.09 [18] All values (mean ± SD) are given in s. Multi-slice data refer to the same section. (Top left) Single-shot proton density (first section) and (top right to bottom right) simultaneous multi-slice T1 maps at 1.5 mm resolution obtained for human liver (healthy subject).…”
Section: Discussionmentioning
confidence: 99%
“…In humans, good reproducibility has been confirmed in healthy volunteer (HV) studies [6]. For example, in a recent study, a coefficient of variance of 9.2 and 7.1% for cortical perfusion and whole kidney perfusion was demonstrated [7]. A small number of studies have shown reduced perfusion in patients with CKD compared to controls [8,9], and in poorly functioning kidney transplants compared to transplants with better function [10,11,12].…”
Section: Introductionmentioning
confidence: 86%
“…A good repeatability of the perfusion measurements (reported as coefficient of variation, CV) was found over the cortex [29,32,33,34] (CV = 4-16%) and the whole kidney [33,34] (CV = 3-7%), while the data for the renal medulla are sparse [34]. A good correlation of the cortical renal blood flow (RBF) was found for ASL and DSC MRI [29,35] in healthy volunteers.…”
Section: Renal Asl Mri In Healthy Volunteersmentioning
confidence: 99%